Network ties, entrepreneurial creativity and competitive advantage: the moderating role of knowledge integration capability - Juniariani, Ni Made Rai; Agustia, Dian (Business: Theory and Practice, 2024)
This study aims to examine the moderating effect of knowledge integration capability on the relationship between business ties, political ties, and entrepreneurial creativity on competitive advantage. We present the first model that links the ability to integrate knowledge, network ties, and entrepreneurial creativity with the background of MSMEs in Indonesia. This study’s data collection method is a questionnaire survey given to Indonesian MSME entrepreneurs. Meanwhile, 358 questionnaires have been qualified for further processing as part of the random sampling approach used in this study’s sample collection. Additionally, the survey data were acquired through the use of SmartPLS, and the study’s findings indicate that business ties, political ties, and entrepreneurial creativity all favorably impact competitive advantage. Knowledge integration capability reinforces the influence of business ties and entrepreneurial creativity on competitive advantage. But knowledge integration capability is unable to counteract the impact of political ties on competitive advantage. The results complement the literature related to the use of knowledge resources in achieving competitive advantage. Considering the important role of knowledge integration capability in the escalation of competitive advantage in corporations, MSME entrepreneurs are strongly advised to consider the available resource of knowledge. To preserve the competitive advantage, knowledge should be continuously expanded.